Dive depth and plumage air in wettable birds: the extraordinary case of the imperial cormorant - Quintana, Flavio Roberto (2007)
Cormorants are considered to be remarkably efficient divers and hunters. In part, this is due to their wettable plumage with little associated air, which allows them to dive with fewer energetic costs associated with buoyancy from air in the feathers. The literature attributes particularly exceptional diving capabilities to cormorants of the ‘blue-eyed’ taxon. We studied the diving behaviour of 14 male imperial cormorants Phalacrocorax atriceps (included in the blue-eyed taxon) in Patagonia, Argentina, and found that this species did indeed dive deeper, and for longer, than most other non-blue-eyed cormorant species. This species also exhibited longer dive durations for any depth as well as longer recovery periods at the surface for particular dive durations. We propose that this, coupled with atypically long foraging durations at sea in cold water, suggests that cormorants of the blue-eyed complex have a plumage with a substantial layer of insulating air. This is given credence by a simple model. High volumes of plumage air lead to unusually high power requirements during foraging in shallow, warmer waters, which are conditions that tend to favour wettable plumage. However, deep dives and/or cold water should favour the blue-eyed phenotype, which explains their essentially high latitude distribution.